(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article provides a philosophical analysis of the transformation of existential structures of human existence in the context of algorithmic rationality in the digital age. Algorithmic rationality is interpreted not merely as a technical instrument but as a new ontological framework that establishes an “ontology of transparency,” within which human behavior is understood as a computable process. In dialogue with existential philosophy (Kierkegaard, Heidegger, Sartre), the categories of freedom, anxiety, guilt, projectivity, meaning, and responsibility are examined. The study argues that these existential structures do not disappear in digital environments but undergo transformation, revealing the limits of reducing subjectivity to probabilistic models. Responsibility, understood as an act of authorship, is identified as the boundary of algorithmic ontology and a condition for preserving subjectivity in the twenty-first century.